2011
DOI: 10.1007/s00191-011-0245-1
|View full text |Cite
|
Sign up to set email alerts
|

Labor market integration policies and the convergence of regions: the role of skills and technology diffusion

Abstract: We study the role of different labor market integration policies on economic performance and convergence of two distinct regions in an agent-based model. Due to a complementarity between the cost saving nature of capital goods with a higher quality and specific skills needed to fully exploit the technologically advanced capital stock, distinct labor market policies result in non-trivially different outcomes. We show that various labor market integration policies yield via differing regional worker flows to dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(19 citation statements)
references
References 18 publications
0
19
0
Order By: Relevance
“…Agent-based models can also be used to approximate the effects of labour market reforms upon unemployment and income inequalities (Dosi et al 2016). Other examples can be found in Dawid et al (2012Dawid et al ( , 2014, where an agent-based model is applied to analyse the convergence of regions characterized by local labour markets and heterogeneous skills. All these areas benefit from the bottom-up approach, in which we only need to understand the behaviour of the agents, i.e.…”
Section: Agent-based Modelsmentioning
confidence: 99%
“…Agent-based models can also be used to approximate the effects of labour market reforms upon unemployment and income inequalities (Dosi et al 2016). Other examples can be found in Dawid et al (2012Dawid et al ( , 2014, where an agent-based model is applied to analyse the convergence of regions characterized by local labour markets and heterogeneous skills. All these areas benefit from the bottom-up approach, in which we only need to understand the behaviour of the agents, i.e.…”
Section: Agent-based Modelsmentioning
confidence: 99%
“…Rather, we describe only the main aspects of the model, which are crucial for the understanding of the mechanisms driving the policy results discussed below. The description of the model is to a large extent identical to the ones given in Dawid et al (, , ), since the multiregional setup used here is similar to that underlying those previous analyses. However, the policy agenda of this paper is quite different from the earlier contributions, which focus on the comparison of different variants of cohesion policies.…”
Section: The Modelmentioning
confidence: 88%
“…Our simulation model has been shown to reproduce a large set of empirical stylized facts on different levels of aggregation. In this contribution and unlike previous policy analyses that we have conducted with the Eurace@Unibi model (see, e.g., Dawid, Gemkow, Harting, Neugart, Kabus, & Wersching, ; Dawid, Gemkow, Harting, & Neugart, , Dawid, Harting, & Neugart, ), we consider a setting where the economy consists of a core region and a periphery region, which differ both with respect to size and their (initial) level of technology. The average quality of the physical capital endowment and the specific skills are initially substantially larger in the core region.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These effects are due to the technological spillovers through the labor market and demand induces investment incentives for producers in that region. Using the same framework, Dawid et al (2011b) also looked into labor market integration policies establishing a trade-off between aggregate output and convergence of regions. There, it is shown that closed labor markets result in relatively high convergence but generate low output while more integrated labor markets yield higher output but lower convergence.…”
Section: Addressing Stylized Facts Of Labor Marketsmentioning
confidence: 99%